Organizational communication and sustainable development ICTs for mobility - Hallin, Anette, 1969-; Gustavsson, Tina Karrbom, 1973-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"This book covers the use, effects, potentials and limitations of new technology for information and communication in social settings and aims to develop an understanding of different perspectives of sustainable development"--Provided by publisher.
Section 4. Critical Perspectives -- 13. Communication, Information and Sustainability: A Geographical Perspective on Regional Communication Policies -- 14. African Families Faced with NICT: Stakes and Effect on Inter-Individual and Intergenerational Relation -- 15. Gender and Technology: Mind The Gap! -- Compilation of References -- About the Contributors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 13, 2010).
Keywords: Communication in organizations; Corporate governance; Management information systems; Sustainable development; Communicating in multicultural firms; Communication in global development projects; Gender and technology; Geographical perspectives on regional communication policies; Green urban planning; ICT and environmental management practice; ICTs for business enterprise mobility; Philanthropy, CSR, and sustainability; Tools for corporate assessment of sustainable development; Workplace location and ICTs; Electronic books